INFLUENCE OF PH ON THE PROPORTION OF UNIONIZED AMMONIA IN RUMEN - RODICA CĂPRIŢĂ; JANA STĂNCULEȚ; D. DRINCEANU; A. CĂPRIŢĂ; I. BENCSIK (Scientific Papers Animal Science and Biotechnologies, 2023)
Protonation and deprotonation of ammonia provides a mechanism for movement of the molecule across membranes and they make ammonia an important intermediate in acid-base regulation as well as N metabolism. Only unionized ammonia molecules are able to penetrate the rumen wall proportional to their concentration. Rising pH dramatically increases the percentage of unionized ammonia. The ratio of the ammonium ion, NH4 + , to ammonia, NH3 is inversely related to pH. The study had in view to establish the content of free and ionized ammonia in the rumen fluid under the influence of nutritional factors (slow release urea, sugar, live yeasts and premix) in five periods. Each increase in pH by 0.5 units further increases free ammonia percentage by the average factor of 3.27. The decrease in pH with 0.5 units from 6.8 to 6.3 induces an increase in the NH4 + proportion from 99.0% to 99.7% while the decrease in pH with 0.5 units from 6.3 to 5.8 induces an increase in NH4 + proportion from 99.7% to 99.9%.